Місце сторітеллінгу у розробці ефективного дизайну - Огієнко, А. Є.; Колендовська, М. М. (ХНУРЕ, 2022)
Storytelling - the technology of creating a story and transmitting the necessary information to influence the emotional, motivational, cognitive sphere of the user. With its help, professionals in the field of visual content and design have the opportunity to communicate, share information and establish relationships with the user. This is a universal tool for creating the right impression of the product.